Software Engineering, Artificial Intelligence, Networking and Parallel/Distributed Computing 2010 - Lee, Roger; Ma, Jixin; Bacon, Liz.; Du, Wencai; Petridis, Miltos; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
The purpose of the 11th Conference Software Engineering, Artificial Intelligence, Networking, and Parallel/Distributed Computing (SNPD 2010) held on June 9 - 11, 2010 in London, United Kingdom was to bring together scientists, engineers, computer users, and students to share their experiences and exchange new ideas and research results about all aspects (theory, applications and tools) of computer and information science, and to discuss the practical challenges encountered along the way and the solutions adopted to solve them. The conference organizers selected 15 outstanding papers from SNPD 2010, all of which you will find in this volume of Springer$1 (Bs Studies in Computational Intelligence.s
Shape Decomposition for Graph Representation -- Improving Accuracy of an Artificial Neural Network Model to Predict Effort and Errors in Embedded Software Development Projects -- From Textual Use-Cases to Component-Based Applications -- COID: Maintaining Case Method Based on Clustering, Outliers and Internal Detection -- Congestion and Network Density Adaptive Broadcasting in Mobile Ad Hoc Networks -- Design and Performance Evaluation of a Machine Learning-Based Method for Intrusion Detection -- Evolution of Competing Strategies in a Threshold Model for Task Allocation -- Efficient Mining of High Utility Patterns over Data Streams with a Sliding Window Method -- Resolving Sluices in Urdu -- Context Sensitive Gestures -- A Recommendation Framework for Mobile Phones Based on Social Network Data -- Language Modeling for Medical Article Indexing.
Keywords: Engineering; Artificial intelligence; Engineering; Computational Intelligence; Artificial Intelligence (incl. Robotics).